1997
DOI: 10.1002/(sici)1096-9136(199706)14:6<449::aid-dia367>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy assessed by fundus photography in Pima Indians with impaired glucose tolerance and NIDDM

Abstract: In a population‐based epidemiological study, 991 Pima Indians with non‐insulin‐dependent (Type 2) diabetes mellitus (NIDDM) and 288 without diabetes aged ≥15 years were examined for retinopathy by fundus photography with a 45° fundus camera after mydriasis. The photographs were graded using a modified Airlie‐House classification scheme. The associations of several factors with retinopathy were studied by logistic regression. Non‐proliferative retinopathy was present in 11.2 % (19/169) subjects at the time of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 3 publications
8
31
0
2
Order By: Relevance
“…There are also reports of differences in prevalence of retinopathy according to ethnicity, with a higher prevalence reported among Mexican Americans (41.3%) and non-Hispanic blacks (30.4%) than in non-Hispanic whites (15.5%) at a diabetes duration of 5-14 years (34). Prevalence of diabetic retinopathy among Pima Indians is estimated at 37.8% with a mean duration of diabetes of 9 years (35). The prevalence in this study is somewhat lower (25.5%).…”
Section: Diabetes Vol 56 April 2007supporting
confidence: 87%
“…There are also reports of differences in prevalence of retinopathy according to ethnicity, with a higher prevalence reported among Mexican Americans (41.3%) and non-Hispanic blacks (30.4%) than in non-Hispanic whites (15.5%) at a diabetes duration of 5-14 years (34). Prevalence of diabetic retinopathy among Pima Indians is estimated at 37.8% with a mean duration of diabetes of 9 years (35). The prevalence in this study is somewhat lower (25.5%).…”
Section: Diabetes Vol 56 April 2007supporting
confidence: 87%
“…However, doing this might also make our population seem healthier than those of other studies, and accordingly weaken the comparability between our study and other similar studies. 12,26 Third, we could not research all possible risk factors including gender, 14,15 duration of pre-diabetes, and hyperglycemia-related inflammatory factors SDF-1a, ICAM-1, and MCP-1. 7 Therefore, perhaps we have missed some potential risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…25,45,52,60,61,[65][66][67]69,70,124,126,141,146,164 Of these, only five were comparative studies between ethnic groups. 52,65,67,69,70 One study reported a similar prevalence in Hispanics and non-Hispanic whites, 52 whereas the remaining four reported differences between blacks, whites, Mexicans, and Hispanics.…”
Section: Ethnic Variationmentioning
confidence: 99%